The Structure Basis of Phytochemicals as Metabolic Signals for Combating Obesity - Li, Xiaoping; Zheng, Liufeng; Zhang, Bing; Deng, Ze-Yuan; Luo, Ting (Frontiers in Nutrition, 2022)
The consumption of phytochemicals, bioactive compounds in fruits and vegetables, has been demonstrated to ameliorate obesity and related metabolic symptoms by regulating specific metabolic pathways. This review summarizes the progress made in our understanding of the potential of phytochemicals as metabolic signals: we discuss herein selected molecular mechanisms which are involved in the occurrence of obesity that may be regulated by phytochemicals. The focus of our review highlights the regulation of transcription factors toll like receptor 4 (TLR4), nuclear factor (erythroid-derived 2)-like 2 (Nrf2), the peroxisome proliferator-activated receptors (PPARs), fat mass and obesity-associated protein (FTO) and regulation of microRNAs (miRNA). In this review, the effect of phytochemicals on signaling pathways involved in obesity were discussed on the basis of their chemical structure, suggesting molecular mechanisms for how phytochemicals may impact these signaling pathways. For example, compounds with an isothiocyanate group or an α, β-unsaturated carbonyl group may interact with the TLR4 signaling pathway. Regarding Nrf2, we examine compounds possessing an α, β-unsaturated carbonyl group which binds covalently with the cysteine thiols of Keap1. Additionally, phytochemical activation of PPARs, FTO and miRNAs were summarized. This information may be of value to better understand how specific phytochemicals interact with specific signaling pathways and help guide the development of new drugs to combat obesity and related metabolic diseases.